Educação na Federação Brasileira: federalismo, laicidade e religião - Carvalho, Carlos Henrique de; Gonçalves Neto, Wenceslau (Acta Scientiarum. Education, 2016)
Acta Scientiarum. Education v. 38, n. 2, 2016